The Effect of Providing Liquid Organic Fertilizer in the Form of Cow Manure on Spinach Plant Growth and Production Red (Amaranthus Tricolor L.) - Ikhwan Riyaldi Siregar (Bioedunis Journal, 2023)
This study aims to determine the effect of applying and the type of liquid organic fertilizer that is best used for cultivating spinach plants. The type of soil used at the research site was sandy loam soil. This research was carried out in one of the houses located at Jalan Raja inal siregar LK 3 Siparau Batunadua Julu sub-district, Padangsidempuan City from November 18 to December 18 2022.Red Spinach is a popular vegetable in Indonesia whose demand will increase every year to keep pace with people's needs. This study aims to determine the effect of POC on the growth and production of spinach plants and the concentration of POC that gives the best effect and the highest yield on the growth and production of red spinach plants. This research was conducted using a randomized block design with four treatments: V0 = without application of liquid organic fertilizer (control), V1 = 20 ml.plant-1 , V2 = 40 ml.plant-1 , and V3 = 60 ml plant-1 , each treatment was repeated four times. The results showed that liquid organic fertilizer from cow manure had an effect on the growth and production of red spinach plants where the POC concentration that gave the best results and the highest yield was 60 ml.plant-1.